Job Creation Law In Proving Ease Of Doing Business In Investment Companies That Conduct Business Activities In Territory Of Indigenous Peoples (Faculty of Law, Universitas Negeri Semarang, 2022)
The Job Creation Law was formed using the omnibus law method to achieve its goals to make changes to various laws and regulations equivalent to it to achieve the Law's goals. Unfortunately, there are problems in regulations that cause Indigenous Peoples and their traditional rights to become unprotected, causing legal uncertainty for investment companies that are reluctant to carry out their business activities in Indigenous Peoples territory. This can hamper the realization of the ease of doing business that the Job Creation Law intends to achieve. Therefore, the Job Creation Law should review the regulations regarding investment companies' activities that carry out their activities in Indigenous Peoples. The research method used is the normative juridical which emphasizes in secondary data method aiming to look for the role of the Job Creation Law to provide legal protection for Indigenous Peoples while providing legal certainty and doing business to investors who carry out business activities in Indigenous Peoples territory. To provide business convenience for these companies and protect Indigenous Peoples traditional rights, the Job Creation Law should change the provisions in the Village Law.